Ανάπτυξη κατανεμημένου συστήματος εξυπηρετητών - Σαρρή, Γεωργία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2016)
This thesis was developed as a part of a larger project, the CoherentPaas, which intends for the integration of a diversity of SQL engines as well as no-SQL data stores in a single cloud PaaS. All these systems will be programmed by using a cloud multi-datastore query language (CloudMdsQL) under a uniform paradigm, and a scalable transactional management system will provide holistic coherence across data stores. This deliverable analyzes the current state-of-the-art of the three data stores (graph database, key-value and document) with respect to the requirements of this project, and then, for each data store, it identifies and proposes the changes required to adapt it to a cloud PaaS. In particular, a network of servers was developed following the master-worker model to act as a middleware between the clients and the database. The clients send the queries to the servers and they process them and send them to the database. One master is elected, whose job is to assign the right server to a client. Furthermore two extra tools were used; Apache Zookeeper was used in order to maintain the synchronization among the servers and the master and Apache Avro was used to handle the communication between all the participants.